2009
DOI: 10.1002/ejic.200900205
|View full text |Cite
|
Sign up to set email alerts
|

Competing Large and Small Angles in a Double End‐On Azido Copper(II) Binuclear Complex: A Combined Experimental and Theoretical Study of Magnetic Interactions

Abstract: The structure and magnetic properties of double azidobridged Cu II binuclear complex 1 with the chelating chiral ligand (S,S)-2,2Ј-isopropylidenebis(4-phenyl-2-oxazoline) were analyzed by combining experimental and theoretical techniques. The Cu II ions adopt a square pyramidal geometry with different degrees of distortion, whereas the two endon azido bridges disposed at the equatorial positions exhibit significantly different Cu-N-Cu angles, 110.6 and 97.3°, which are respectively smaller and larger than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] In addition to the terminal monodentate nature of the azido ligand [1][2][3][4] many bridging coordination modes were reported where a magnetic super-exchange mechanism is known to occur through various modes. [5][6][7][8][9][10][11][12][13][14][15][16] These include single and double μ 1,3 -N 3 (end-to-end, EE) [5][6][7][8][9][10][11][12][13][14][15][16][17] and μ 1,1 -N 3 (endon, EO), [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] μ 1,1,3 -N 3 , μ 1,1,1 -N 3 ...…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In addition to the terminal monodentate nature of the azido ligand [1][2][3][4] many bridging coordination modes were reported where a magnetic super-exchange mechanism is known to occur through various modes. [5][6][7][8][9][10][11][12][13][14][15][16] These include single and double μ 1,3 -N 3 (end-to-end, EE) [5][6][7][8][9][10][11][12][13][14][15][16][17] and μ 1,1 -N 3 (endon, EO), [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] μ 1,1,3 -N 3 , μ 1,1,1 -N 3 ...…”
Section: Introductionmentioning
confidence: 99%
“…The crossover from FM to AF is in good agreement with that predicted for double-azide-bridged Cu II dimers using DFT calculations. [23] Obviously, the FM interaction observed in the tetrazolate-bridging compound 1, which has f= 1168, does not follow this trend. We note that the azide bridge at this angle induces AF coupling, as suggested by experimental and theoretical studies, [23] and that the tetrazolate N-N bridge induces weak AF coupling, as indicated by a recent Cu II dinuclear compound with a double tetrazolate bridge.…”
Section: Magnetic Propertiesmentioning
confidence: 95%
“…[23] Obviously, the FM interaction observed in the tetrazolate-bridging compound 1, which has f= 1168, does not follow this trend. We note that the azide bridge at this angle induces AF coupling, as suggested by experimental and theoretical studies, [23] and that the tetrazolate N-N bridge induces weak AF coupling, as indicated by a recent Cu II dinuclear compound with a double tetrazolate bridge. [24] Orbital counter-complementarity [12a,b, 25] of the two dissimilar bridges may be evoked to explain the overall FM coupling observed in 1.…”
Section: Magnetic Propertiesmentioning
confidence: 95%
“…Therefore, the exchange interactions through the interchain EE-azide bridge (J 3 ) should be low. Secondly, in the double EO-azide-bridged dinuclear core, the magnetic 3d [32,33] and are known to be correlated to the Cu-N azide -Cu angle (θ). As θ increases from about 85 to 104°, J gradually decreases, and finally enters the antiferromagnetic regime (J Ͻ 0) when θ Ն104°.…”
Section: Magnetic Propertiesmentioning
confidence: 99%